Antifungal compound and its production - Seow, Heng Fong; Jee, Jap Meng; Ho, Coy Choke; Cheah, Hwen Yee (2010)
The invention relates to a compound for the preparation of a medicament, and methods of obtaining the compound a product of the microorganism. In particularly, the present invention relates to the anti-fungal effects pharmaceutical composition, medicament or method of treatment related to said compound of the invention are for the treatment of diseases associated with fungus or yeast.